DEVOTOS DO SIGMA: INTEGRALISTAS DE TEIXEIRA SOARES/PR, 1935-1938 - Oliveira, Luiz Gustavo de (2015)
The research discusses the integralist political experience in the city of Teixeira Soares, from the base of militancy, the experience of power, until the end of the Brazilian Integralist Action (BIA) with the beginning of the "New State". Teixeira Soares, located in the region of Campos Gerais, Paraná State, was the first city to electing an integralist mayor in Brazil. We analyze the daily practices of the local BIA members and their relationships with Integralists cores from other cities and state and national representatives of the movement between the years 1935 and 1938. The presence of the sigma in the locality originated political dissentions involving families, friends and permeated the whole society. The Integralists times in Teixeira Soares inflamed the souls of the inhabitants, marked the everyday life of the small town and its rural districts with speeches, rituals, symbols, persecutions and victories, moving reasons and sensibilities.